Opinion toward online learning during COVID-19 pandemic among students and lecturers at the faculty of nursing in a private university - Permwongk, Chudapa; Tumwijit, Saimai; Charoenbhakdi, Jeuajan; Prewnim, Arpakorn; Deemuang, Jiraporn (Thai Journal of Nursing, 2023)
The descriptive research aims to study opinion toward online learning during COVID-19 pandemic among students and lecturers at the faculty of nursing in a private university. A sample of 219 students and 25 lecturers was purposively selected. Research instruments were questionnaires on opinion toward online learning during COVID -19 pandemic for students and for lecturers. Their reliability coefficients were 0.81 and 0.78 respectively. The results are as follows. 1) Nursing students’ opinion toward online learning during COVID-19 pandemic, are at a moderate level, but lecturers’opinion are at a high level. 2) In the subpart of attitude toward benefits of online learning, their opinion are at a high level in both groups of students and lecturers. In the subpart of problem during online learning, their opinion are at a moderate level in both groups of students and lecturers. In the subpart of activities/problems of online learning, students’ opinion are at a moderate level but lecturers’ opinion are at a high level.